Development of a specific MPXV antigen detection immunodiagnostic assay - Davis, Ian; Payne, Jackie M.; Olguin, Victoria L.; Sanders, Madison P.; Clements, Tamara; Stefan, Christopher P.; Williams, Janice A.; Hooper, Jay W.; Huggins, John W.; Mucker, Eric M.; Ricks, Keersten M. (Frontiers in Microbiology, 2023)
Human monkeypox (mpox) has recently become a global public health emergency; however, assays that detect mpox infection are not widely available, largely due to cross-reactivity within the Orthopoxvirus genus. Immunoassay development was largely isolated to the researchers who focus on biothreats and endemic areas (Central and West Africa) until the 2022 outbreak. As was noted in the COVID-19 pandemic, antigen detection assays, integrated with molecular assays, are necessary to help curb the spread of disease. Antigen detecting immunoassays have the benefit of giving results in minutes-to-hours and in lateral flow formats, they can be deployed to point of care, home, or field use. This work reports the development of an mpox-specific antigen-detection immunoassay developed on a multiplexed, magnetic bead-based platform utilizing reagents from all research sectors (commercial, academic, and governmental). Two semi-quantitative assays were developed in parallel and standardized with infectious mpox virus (MPXV) cell culture fluid and MPXV positive non-human primate (NHP) sera samples. These assays detect viral antigen in serum, were highly specific toward MPXV as compared to other infectious orthopoxviruses (vaccinia virus, cowpox virus, and camelpox virus), and correlated to quantitative PCR results from an NHP study. Access to a toolbox of assays for mpox detection will be key for identification of cases and proper treatment, as MPXV is now a global traveler.